Impact of Korean dramas on Nanyang Technological University Nanyang Business School undergraduates. - Sng, Eddy Shih Wei. (2008)
The main aim of the study wass to find out how dramas can be used as an advertising tool for tourism. In view of the new phenomenon Korean wave, which successfully used Korea dramas to promote Korea as a tourist destination, Korean dramas were selected as the basis of the study. In addition, the study aimed to find out the critical success factors used in the Korean dramas that made them an effective advertising tool for Korean tourism.